Father Brown. Season six [videorecording (DVD)] - Gibson, Paul (Director); Williams, Gary; Williams, Mark, 1959-; Cusack, Sorcha, 1949-; Carroll, Nancy, 1974-; Chesterton, G. K. (Gilbert Keith), 1874-1936 (BBC, 2018)
Set in a 1950s English village, Father Brown uses theology and his love and understanding of other people to solve crimes.